Oocyte morphometry in female dogs (Canis familiaris, Linnaeus, 1758) - Diagone, K. V. [UNESP]; Vicente, W. R. R. [UNESP]; Pacheco, M. R. [UNESP]; Mateus, O. [UNESP] (Blackwell Publishing, 2008)
In the present study, the ovaries of 15 healthy bitches divided into three groups according to age were analysed by histology and morphometry: group 1 (1-3 years), group 2 (> 3-5 years) and group 3 (> 5-7 years). After ovariosalpingohysterectomy, the ovaries were fixed, routinely processed for embedding in paraffin and stained with haematoxylin-eosin. The following morphometric parameters were analysed: maximum and minimum diameter (mu m), perimeter (mu m), area (mu m(2)) and roundness of the cytoplasm and nucleus of oocytes from different types of follicles. Significant differences in the cytoplasmic and nuclear parameters of follicular oocytes between the experimental groups were determined by ANOVA and the Tukey test (5%). For the biotechnology of reproduction, the present results showed that in vitro maturation yielded the best performance for oocytes from primordial follicles in group 3 females and for oocytes embedded in secondary and tertiary follicles in group 2 females. In addition, the present findings will help in the diagnosis and prognosis of diseases affecting bitches, and will especially contribute to a better understanding of these cells by researchers in the field of histology and canine reproduction.